High seroprevalence of dengue virus indicates that dengue virus infections are frequent in central and eastern Sudan. Issue 9 (5th July 2018) - Adam, Awadalkareem; Schüttoff, Tom; Reiche, Sven; Jassoy, Christian
Abstract: Objectives: To determine the seroprevalence of dengue in central and eastern Sudan and the breadth of neutralising antibody responses. Methods: Blood was drawn from 483 patients with fever who visited outpatient clinics in Port Sudan, Red Sea state, in three towns in Kassala state and in El Obeid, North Kordofan, in December 2012 and January 2013. Sera were tested for dengue virus IgG and IgM by ELISA (Panbio) and sera without serologic evidence of acute infection (IgM negative) were used for the analysis of the seroprevalence. DENV neutralisation tests were performed to determine the specificity of the ELISA and to examine the degree of cross‐neutralisation of multiple DENV serotypes. Results: Sixty‐seven per cent (302 of 448) of the sera were dengue virus IgG‐positive. The seroprevalence in Port Sudan was 89% (106 of 119 sera), in Kassala 61% (128 of 209) and in North Kordofan 56.7% (68 of 120). Thirty‐one of 32 ELISA‐positive sera neutralised dengue viruses indicating that the ELISA was highly specific. The majority of the sera broadly neutralised all four dengue virus serotypes indicating multiple infections. Conclusions: The majority of the population in central and eastern Sudan has been infected with dengue viruses, many people repeatedly. The high seroprevalence underscores the need for extended dengue surveillance in Sudan, broad disease awareness in medical institutions and in the population and diagnostic capacity building for severe dengue infections.